Identitat i alteritat en les novel·les de Carme Riera - Gregori, Carme (Caplletra. Revista Internacional de Filologia, 1997)
The article analyses the theme of identity in the first two novels of Carme Riera: Una primavera per a Domenico Guarini i Joc de miralls, a theme which is based on the path to personal maturity in the first novel and on motive of the double in the latter.